Modulation of radiotherapy- and chemotherapy-induced normal tissue response as prophylaxis of their side effects - Plevová, Pavlína (Radiology and oncology (Ljubljana), 2002)
Background. Ionising radiation and cytostatic agents used in cancer therapy induce an immune response in normal tissues mediated by cytokines and adhesionmolecules. Strategies modulating this response may downregulate cancertherapy side effects. The data published on the given topic have been reviewed. Conclusions. The strategies influencing the tissue immune response with the aim to reduce the side effects of chemotherapy and radiotherapy are conflicting. Some of them inhibit this response supposing that an exaggerated reaction may have a damaging effect (e.g. corticosteroids, nonsteroidal anti-inflammatory drugs (NSAID), lisofylline, anti-cytokine antibodies, anti-sense oligonucleotides, sialyl Lewis X analogues), others promote this reaction by inducing endogenous production of cytokines (AS101) or use recombinant forms of appropriate cytokines involved in this response in order to intensify the physiologic tissue response. In clinical practice, corticosteroids and NSAID are widely used to modulate this response, while other agents are still experimental.
Keywords: Adjuvants, immunologic; Adverse effects; Antineoplastic agents; Antineoplastiki; Drug therapy; Imunostimulatorji; imunski odziv; kemoterapija; Neoplasms; Novotvorbe; onkologija; Radioterapija; Radiotherapy; therapy; tumor; zdravljenje